Determinants of E-Learning System Adoption among Ghanaian University Lecturers: An Application of Information System Success and Technology Acceptance Models - Opoku, Daniel; Pobee, Frederick; Okyireh, Rexford Owusu (American Journal of Social Sciences and Humanities, 2020)
This study aims at exploring the factors that influence e-learning adoption among university lecturers. It is realised that the adoption rate of e-learning in the context of developing countries is very low and this has called for more research. A sample size of 131 respondents was selected using both convenience and purposive sampling technique. Questionnaires were used to elicit information from respondents. Data analysis was performed using SPSS and SmartPLS application. The study found eight of the eleven hypotheses tested to be statistically significant whiles the remaining three factors were found to be statistically insignificant. This study is limited to only one university (University of Ghana, Legon). Sakai is a software used by both students and lecturers to facilitate distance learning. So, the concentration of the analysis on just lecturers may not give the clearest picture of the adoption of the software. The results of this study will help developers of an e-learning system to improve users’ adoption by critically looking at these factors. Sufficient support and training should also be provided to both administrators and instructors to improve their adoption of rate. This study is one of the first kind to investigate university lecturers’ e-learning adoption specifically in a Ghanaian University by applying the Information System Success and Technology Adoption Models. The study, therefore, contributes to the research gap on the lack of e-learning studies in developing countries that have emphasized the use of eLearning systems.